Endya ennungi eri abakyala abali mu myaka egizaala - CGIAR Initiative on Sustainable Animal Productivity (International Livestock Research Institute, 2024)
Although smallholder farmers are key producers of livestock, many of their households still experience high levels of malnutrition. To address this paradox, the ILRI Uganda office partnered with the Ministry of Health to develop an innovative communication package focused on improving nutrition.